PENGARUH MODEL PEMBELAJARAN PROJECT BASED LEARNING DAN PENGETAHUAN AWAL TERHADAP HASIL BELAJAR MATA PELAJARAN SENI BUDAYA BIDANG SENI RUPA SISWA KELAS VII DI SMP NEGERI 2 PADANG - Novenda Exsi Milyani, Dr. Ramalis Hakim, M.Pd., Drs. Wisdiarman, M.Pd. (Universitas Negeri Padang, 2018)
This study aims to determine the effect of Project Based Learning and Prior Knowledge learning model on the result of VII grade students in SMP Negeri 2 Padang on art and culture subjects in art study. The type of this research is quantitative research with quasi-experimental form. Population in this research is all class of VII grade that exist in SMPN 2 Padang, while VII.2 and VII.7 are taken as the sample. The data which is needed in this research are primary data in the form of preliminary knowledge test result and students learning result test. The data is analyzed by using t-test. The finding of the research shows that 1) there are differences of students' learning outcomes that are taught by using the Project Based Learning with student learning outcomes taught by using conventional learning model, 2) there are differences in students` learning outcomes who have high initial ability taught by using Based Project Learning with the ones who taught by using conventional learning model, 3) there are differences in students` learning outcomes who have low initial ability taught by using learning Based Project Learning with the ones who taught by using conventional learning model. Based on the result, it is concluded that Project Based Learning as one of the learning model has a positive effect on student learning outcomes.Keywords: Project Based Learning, Learning Model, Learning Outcomes, Education, Prior Knowledge